2022
DOI: 10.1155/2022/4033886
|View full text |Cite|
|
Sign up to set email alerts
|

The Application of a Computer Monitoring System Using IoT Technology

Abstract: Through the information exchange of the Internet of Things, resources in multiple fields can be integrated to provide users with more comprehensive, diverse, and high-quality services. The computer monitoring system can effectively improve the intelligence and networking of the office and is widely used in many industries. The application of Internet of Things technology can effectively improve the intelligence and networking of computer monitoring systems. The Internet of Things technology can realize the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Tere are some shortcomings in this study. (1) Due to the updating of technology, the convergence and quasi-combination of the algorithm do not reach the optimal solution. At the same time, the degree of matching of diferent data types to the algorithm is not nearly the same, which needs more detailed research in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tere are some shortcomings in this study. (1) Due to the updating of technology, the convergence and quasi-combination of the algorithm do not reach the optimal solution. At the same time, the degree of matching of diferent data types to the algorithm is not nearly the same, which needs more detailed research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The explosive prosperity of Internet of things technology and artificial intelligence has promoted profound changes in the industry worldwide [ 1 ]. Information resources are gradually becoming one of the most essential strategic resources.…”
Section: Introductionmentioning
confidence: 99%
“…The computer-based monitoring systems can be effectively enhanced by utilizing the application of Internet of Things (IoT) technology [14]. Jozsef Katona et al developed a technique in 2019 in the field of BCI.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%